Chemical composition and anticancer activities of methanol-extracted agarwood (Gyrinops verstegii [Gilg.] Domke). Issue 1 (November 2021) - Waluyo, T K; Pasaribu, G; Winarni, I
Abstract: This research aimed to study about chemical composition and anti-cancer activities of natural agarwood and cultivated agarwood ( Gyrinops vertegii [Gilg.] Domke). Agarwood used in the research was of lowest qualities, which comprised agarwood with natural kemedangan type (A), with cultivated kemedangan-I type (B1), and with cultivated kemedangan-II type (B2), all after methanol extraction. Chemical composition was examined using GC-MS instrument, meanwhile tests on lungs associated anticancer activities (A549's cancer cells) were performed using MTT method. Chemical composition in low-quality agarwoods was predominantly sesquiterpene compounds, comprising among others guaiacol, cumene, aromadendrene, aplha-humulene, velleral, etc; and conservely did not contain chromone derivative compounds which are compounds characterizing quality agarwood. Low-quality agarwood extracts afforded efficacious potency as anticancer actions against A549's lungs-attacking cancer cells with IC50 values at 144.92 µgmL −1 (A); IC50 at 206.88 µgmL −1 (B1), and IC50 187.97 µgmL −1 (B2).